Networked insurgence and an anti-electoral democracy: Bangkok space 2014–2020. (June 2022) - King, Ross
Bangkok presents a rich history of popular uprisings directed against its periodic military dictatorships. Then, in 2006 and 2010 there were uprisings of increasing theatricality, playing to a hoped-for global audience, but now against democratically elected governments. January 2014 saw this insurrectional performance art raised to a new plateau where the city itself became the stage and the portrayed villain no longer the government, but government as such— against electoral democracy and for some vague, imagined ideal that might be seen as post-electoral democracy based in civil society rather than political parties. An ensuing military-drafted constitution built on this rejection, leading to manipulated elections in 2019 and a new, quasi-elected, monarchist-military government scarcely understandable outside the context of the dark euphoria of 2014. Then in 2020 the tide of insurgence turned again, against the military hegemony but also against the monarchy—a seismic shift. The paper's focus is on these events of 2014 and their 2020 denouement, also on their implications for both the space and the form of the city in a digital age.